20t(t+3)=19t-20

Simple and best practice solution for 20t(t+3)=19t-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20t(t+3)=19t-20 equation:


Simplifying
20t(t + 3) = 19t + -20

Reorder the terms:
20t(3 + t) = 19t + -20
(3 * 20t + t * 20t) = 19t + -20
(60t + 20t2) = 19t + -20

Reorder the terms:
60t + 20t2 = -20 + 19t

Solving
60t + 20t2 = -20 + 19t

Solving for variable 't'.

Reorder the terms:
20 + 60t + -19t + 20t2 = -20 + 19t + 20 + -19t

Combine like terms: 60t + -19t = 41t
20 + 41t + 20t2 = -20 + 19t + 20 + -19t

Reorder the terms:
20 + 41t + 20t2 = -20 + 20 + 19t + -19t

Combine like terms: -20 + 20 = 0
20 + 41t + 20t2 = 0 + 19t + -19t
20 + 41t + 20t2 = 19t + -19t

Combine like terms: 19t + -19t = 0
20 + 41t + 20t2 = 0

Factor a trinomial.
(5 + 4t)(4 + 5t) = 0

Subproblem 1

Set the factor '(5 + 4t)' equal to zero and attempt to solve: Simplifying 5 + 4t = 0 Solving 5 + 4t = 0 Move all terms containing t to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4t = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 4t = 0 + -5 4t = 0 + -5 Combine like terms: 0 + -5 = -5 4t = -5 Divide each side by '4'. t = -1.25 Simplifying t = -1.25

Subproblem 2

Set the factor '(4 + 5t)' equal to zero and attempt to solve: Simplifying 4 + 5t = 0 Solving 4 + 5t = 0 Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5t = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5t = 0 + -4 5t = 0 + -4 Combine like terms: 0 + -4 = -4 5t = -4 Divide each side by '5'. t = -0.8 Simplifying t = -0.8

Solution

t = {-1.25, -0.8}

See similar equations:

| x/.1=900 | | 80=4x+x+3+5x-3 | | x*.1=900 | | (4x)1/2(2x4/3) | | x-.1=900 | | 129+32x=90+45x | | =(-5)+8 | | 3x+8y+9x= | | 180=75+x+x | | 66=2(2z)+2(11)+2(12)+2(3z-1)+2(z+2) | | 7(x+8)=8+7x+15 | | .5x-1.5+1.5-x=-5x | | .25(3x+1)-.625x=.5x | | 8(2b+7)=4(b+10) | | =1-7 | | 2(x-3)+2(3x-3)=2x+2(2x-1) | | 3(6-z)+6z= | | .1/x=90 | | 2x-22=-3x+28 | | 18-6a=4a-4a-12 | | 3+2[x-9]=12-7x | | .1*x=900 | | X-5+6x-23=3x+2 | | 7x-4(6-x)+12= | | p-9b/13c-7 | | .1-x=900 | | 5(x+4)=-50 | | 5x-13y+10y= | | 56m^13n^6/8m^12n^3 | | 3x-18=-x+30 | | 8(2b-7)=4(b+10) | | 6x-3x-12= |

Equations solver categories